Comparison of Outcome of DHS (Dynamic Hip Screw) Vs Cannulated Screws in Managing Fracture of Neck of Femur - Syed Habib Ullah, Zubair Karim, Mazhar Mahmood, Abdul Munaf Saud, Mohammad Abid, Muhammad Tahir (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: To compare the outcome of DHS (dynamic hip screw) vs cannulated screws in managing fracture of neck of femur. Study Design: Randomized controlled trial. Study Duration: 22-06-2021 to 21-12-2021 (6 months) Settings: Department of Orthopedic, D.G Khan Hospital, D.G Khan. Materials & Methods: A total of 60 patients with fresh fracture neck of femur, 18 to 60 years of age of both genders were included. The DCS group was managed by internal fixation with Dynamic hip screw and CS group was treated by internal fixation with cannulated screws. All patients were followed for 3 months for outcome. Results: Total 60 patients of fracture of femur neck was recruited. Mean age and mean duration of fracture was 44.42 ± 12.45 years and 10.67 ± 5.66 days. In DCS group, mean age and duration of fracture was 44.57 ±11.60 years and 10.23 ± 5.86 days respectively. In CS group, mean age and mean duration of fracture was 44.27 ± 13.46 years and 11.10 ± 5.51 days respectively. In DCS group, satisfactory outcome was found in 25 (83.33%) patients while in CS group, it was found in 13 (43.33%) patients. After applying chi-square test, it was noted that DCS group had significantly (P=0.003) higher proportion of satisfactory outcome as compared to CS group. Conclusion: Results of this study showed that DCS group had significantly higher proportion of satisfactory outcome as compared to CS group in cases of femur neck fractures. Most of the patients were between 41-60 years of age but difference of satisfactory outcome between DHS group and CS group was not significant. Regarding male patients, significantly higher rate of satisfactory outcome was noted in DHS group as compared to CS group. Keywords: femur neck fracture, dynamic hip screw, cancellous screw.